Impact of different emulsifiers on biocompatibility and inflammatory potential of Perfluorohexyloctane (F6H8) emulsions for new intravenous drug delivery systems - Tsagogiorgas, Charalambos; Anger, Friedrich; Beck, Grietje; Breedijk, Annette; Yard, Benito A.; Höger, Simone (Drug design, development and therapy, 2019)
Background: Emulsions on the basis of Perfluorohexyloctane (F6H8), a semifluorinated alkane (SFA), have shown to dissolve and transport highly lipophilic compounds. It is unknown how F6H8-containing emulsions (F6H8-cEM) interact with compartment blood, the reticuloendothelial system (RES), or influence injured organs in vivo. The current study was conducted to investigate the in vitro biocompatibility of F6H8-cEM and their drug delivery properties. Afterward, an in vivo study was performed as a proof-of-concept study in a rat model of acute kidney injury (AKI), which focused on the potential influence of F6H8-cEM on inflammation in an injured organ.Methods: Two different F6H8-cEM were stabilized by the emulsifying agents Poloxamer 188 (Pluronic®, F68) or lecithin (S75). The two resulting emulsions F6H8-Pluronic or F6H8-lecithin were tested in vitro for the potential modulation of acute inflammation via whole blood assay, FACS, and ELISA. Antioxidant capacity and drug delivery properties were measured with an oxidation assay. Secondly, AKI was induced in the rats, which were treated with the F6H8-lecithin emulsion. Renal function and inflammation were assessed.Results: Both F6H8-cEM were phagocytized by monocytes and both dose-dependently affected apoptosis (Annexin V binding) in monocytes. TNF-α expression increased dose-dependency for F6H8-Pluronic emulsion but not for F6H8-lecithin in a whole blood assay. Both F6H8-cEM were able to carry α-tocopherol as a model drug. Animals with AKI treated with the F6H8-lecithin emulsion showed a significantly better renal function and less infiltration of inflammatory cells in renal tissue compared to the control, while inflammatory markers in renal tissue, except HO-1, were not affected by F6H8-lecithin.Conclusions: Pluronic®, F68 does not seem suitable as a biocompatible surfactant for F6H8-cEM. The injured kidney was not negatively influenced by the F6H8-lecithin emulsion. Lecithin-stabilized F6H8-cEM could be tested for preclinical studies as a carrier system for lipophilic agents.Keywords: Perfluorohexyloctane, emulsion, inflammation, drug delivery, acute kidney injury
Gesehen am 15.11.2019